Entertaining Africans: Creative Innovation in the (Internet) Television Space - Dovey, Lindiwe (Television in Africa in the Digital Age, 2021)
Despite great heterogeneity, the vast continent of Africa and the diverse people of its countries and diasporas have often been represented through the most reductive, essentialising, and denigrating paradigms— a process that Nigerian writer Chimamanda Adichie Ngozi has referred to as “the danger of a single story”. One of the most dangerous of these paradigms is the developmentalist one, which shoehorns Africa into a western, capitalist teleological framework that overlooks and denies Africa’s production of and participation in forms of leisure, pleasure and entertainment.
Keywords: 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 3-Afrique (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Identités diasporiques; Royaume-Uni (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

McTV: Understanding the Global Popularity of Television Formats - Waisbord, Silvio (Television & New Media, 2004)
Globalization has intensified interconnectivity among television industries worldwide. Interconnectivity happens through structural and institutional linkages among television systems and industries worldwide, resulting in an increasingly integrated global business governed by similar practices and goals. The dynamics are reflected in the popularity of television formats. On the surface, global dissemination of formats may suggest not only the global integration of the economy of the industry but also the standardization of content. A dozen media companies are able to do business worldwide by selling the same idea, and audiences seem to be watching national variations of the same show. At a deeper level, however, formats attest to the fact that television still remains tied to local and national cultures. Bringing up examples of Latin American cases, this article argues that television is simultaneously global and national, shaped by the globalization of media economics and the pull of local and national cultures.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; Argentine (corpus analysé); Brésil (corpus analysé); Mexique (corpus analysé); Royaume-Uni (corpus analysé); _Nettoyé; États-Unis (corpus analysé); États-Unis (lieu de production du savoir)